Aggressive behavior, boredom, and protective factors among college students during closed-off management of the COVID-19 pandemic in China - Li, Yujie; Chu, Xiaoyi (Frontiers in Psychology, 2022)
Chinese colleges have implemented strict closed-off management in response to the outbreak of a new variant of the new coronavirus, Omicron. But such management measures may lead to more aggressive behavior. The study aimed to determine the associations between boredom and cognitive flexibility with aggression and to examine the impact of boredom on aggression through the moderating role of cognitive flexibility. The Multidimensional State Boredom Scale, the Reactive–Proactive Aggression Questionnaire, and the Cognitive Flexibility Inventory were applied to a sample of 719 college students who were in a closed-off management environment. The results show a significant positive correlation between boredom and aggressive behavior. Cognitive flexibility is found to negatively moderate the relationship between the two means of boredom and aggression. Specifically, a weakening association between boredom and proactive aggression with the introduction of a high cognitive flexibility level was introduced to the model. The findings highlighted the importance of boredom as a potential risk factor to aggression, while cognitive flexibility appears as a potential protective factor.